Immunization Strategies Targeting Newly Arrived Migrants in Non-EU Countries of the Mediterranean Basin and Black Sea - Giambi, Cristina (Int J Environ Res Public Health, 2017)
Background: The World Health Organization recommends that host countries ensure appropriate vaccinations to refugees, asylum seekers and migrants. However, information on vaccination strategies targeting migrants in host countries is limited. Methods: In 2015–2016 we carried out a survey among national experts from governmental bodies of 15 non-EU countries of the Mediterranean and Black Sea in order to document and share national vaccination strategies targeting newly arrived migrants. Results: Four countries reported having regulations/procedures supporting the immunization of migrants at national level, one at sub-national level and three only targeting specific population groups. Eight countries offer migrant children all the vaccinations included in their national immunization schedule; three provide only selected vaccinations, mainly measles and polio vaccines. Ten and eight countries also offer selected vaccinations to adolescents and adults respectively. Eight countries provide vaccinations at the community level; seven give priority vaccines in holding centres or at entry sites. Data on administered vaccines are recorded in immunization registries in nine countries. Conclusions: Although differing among countries, indications for immunizing migrants are in place in most of them. However, we cannot infer from our findings whether those strategies are currently functioning and whether barriers to their implementation are being faced. Further studies focusing on these aspects are needed to develop concrete and targeted recommendations for action. Since migrants are moving across countries, development of on-line registries and cooperation between countries could allow keeping track of administered vaccines in order to appropriately plan immunization series and avoid unnecessary vaccinations.